Cultivable microscopic fungi from an underground chemosynthesis-based ecosystem: a preliminary study - Nováková, Alena; Hubka, Vít; Valinová, Šárka; Kolařík, Miroslav; Hillebrand-Voiculescu, Alexandra Maria (Folia microbiologica, 2018)
Movile Cave, a unique groundwater ecosystem in southern Romania, was discovered in 1986. This chemoautotrophic cave contains an abundant and diverse fauna with terrestrial and aquatic invertebrate communities, including 33 endemic species. Since its discovery, studies have focused mainly on cave chemoautotrophic bacteria, while the microfungal community has been largely neglected. In this study, we determined the microfungal species living on various substrates in Movile Cave and compared this spectrum with the mycobiota detected outside the cave (outside air-borne and soil-borne microfungi). To investigate all of the niches, we collected samples for two consecutive years from the dry part of the cave (cave air and sediment, corroded limestone walls, isopod feces, and isopod and spider cadavers) and from the post-siphon part of the cave, i.e., Airbell II (sediment and floating microbial mat). A total of 123 microfungal species were identified from among several hundred isolates. Of these, 96 species were only detected in the cave environment and not outside of the cave, while 90 species were from the dry part of the cave and 28 were from Airbell II. The most diverse genera were Penicillium (at least 18 species) and Aspergillus (14 species), followed by Cladosporium (9 species). Surprisingly, high CFU counts of air-borne microfungi were found inside the cave; they were even higher than outside the cave during the first year of investigation.
Keywords: chemoautotrofní růst; Phylogeny; Fungi; jeskyně; ekosystém; Chemoautotrophic Growth; houby; Caves; Microscopy; mikroskopie; Ecosystem; fylogeneze